Insights into the link between drug use and criminality: Lifetime offending of criminally-active opiate users. (1st October 2017) - Pierce, Matthias; Hayhurst, Karen; Bird, Sheila M.; Hickman, Matthew; Seddon, Toby; Dunn, Graham; Millar, Tim
Highlights: Over the life-course, opiate users have elevated rates of acquisitive offending. This association exists prior to opiate-initiation. Opiate initiation escalates the difference between opiate users and non-users. This escalation is greater for females and for non-serious acquisitive offences. Abstract: Background: We test whether the offending trajectory of those who test positive for opiates is greater than test-negative controls and whether the relationship is constant both prior to, and post, opiate initiation. We consider whether these relationships differ according to gender and offence type. Methods: The study provides an analysis of historical offending records in adults linked to test results for opiate and cocaine metabolites. Those testing positive for opiates were linked to treatment records to retrieve data on age of opiate initiation. Rate ratios (RR) were calculated to compare opiate positive testers to opiate and cocaine negative controls, separately by gender and adjusting for age and birth cohort. Age of opiate initiation was included in a second model as a time-dependent variable. Within-subject clustering was accounted for using generalised estimating equations. Results: Opiate-positive cases had higher rates of offending than test-negative controls, both prior to, and post, opiate initiation. Initiation of opiate use increased the RR by 16% for males but doubled it for females. The RR increase in non-serious acquisitive crime was greater than that seen in serious crime. For males only, opiate initiation narrowed the difference in violent offending rate between cases and controls. A larger offending increase was associated with opiate initiation in female, compared to male, users. Conclusions: For most crime categories, the difference between groups is exacerbated by opiate initiation. The findings indicate that opiate prevention initiatives might be effective in reducing offending, particularly among females.